Organic Geochemistry and Stable Carbon Isotopes of Oil Seepages in the Abu-Jir Fault Zone at Al-Anbar Governorate, Iraq - M. Awadh , Salih; A. Hussien, Sfoog (Iraqi Journal of Science, 2023)
Oil seep samples along Abu-Jir Fault Zone were studied to determine their chemical characterization and origin. They are dominated by the normal alkanes, more complex mixture of branched and cyclic hydrocarbons. Organofacies coupled with the stable carbon isotopes have been integrated to infer the oil seep origin. Oil seeps contain H2S gas, which derives as a catabolic by product of sulfate-reducing bacteria from gypsum of the Fatha Formation during the early diagenetic under anoxic conditions which is demonstrated by values of C29/H that are greater than 1. The oil seeps are characterized by δ13C values vary from -29.0 to -27.96‰ and from -28.34 to -27.88‰ in the saturated and aromatic compounds, respectively; consequently, they have low values of the canonical variable ranged from -3.47 to -0.17 reflecting a marine non-waxy oil generated from planktonic kerogen of type-II that has been partially mixed with the terrestrial origin. The values of the tricyclic terpanes (C22/C21 and C31R/H) that are higher than 0.5 and 0.25 respectively support the marine source rocks. The Triassic age was suggested for the oil age in the dependence of the occurrence of the aromatic dinosteranes which marked dinoflagellates were participated in the oil derivation.